Investigating product acquisition strategies in closed-loop supply chains - Afshar, Saman (2016)
Remanufacturing is one of the main recovery operations in Closed-Loop Supply Chains (CLSCs) that not only can contribute to a more sustainable environment, but also has significant economic and social benefits. A key factor for having an efficient remanufacturing operation is to control the heterogeneous characteristics of product returns in terms of quantity, quality and timing. Product Acquisition Management is an essential process in CLSCs, which aims to deal with these characteristics of product returns. The present study extends knowledge in Product Acquisition Management, by developing quantitative models that generate meaningful insights into the economics of proactive product acquisitioning. In addition, case studies inform the present study with the current status of product acquisition management in practice and the relevant challenges. The economic-oriented decision about operating a proactive or passive strategy is explored under quantity and quality-based incentive approaches. Closed-form solutions and quality thresholds are derived for the optimal return rate and optimal quality rate that minimises the total cost of the proactive strategy. The analysis of the infinite planning horizon models show that, the optimal acquisition strategy depends on a trade-off between the relevant remanufacturing cost advantage and the acquisition cost structure. A diseconomy of scale in the acquisition of returns leads to a decrease of the remanufacturing amount. Sensitivity analysis further highlights the differences between the quantity and the quality-based incentive approaches. This study extends its investigation on the economic viability of the proactive acquisition strategy under the finite planning horizon. Using the product life cycle as a basis for matching demand and supply, the analysis shows that delays in the processing of returns will reduce the cost advantages of a proactive acquisition strategy and that applying a dynamic acquisition policy will increase the cost improvement of the proactive strategy. Finally, the study investigates a dynamic manufacturing-remanufacturing system with a responsive buy-back policy by considering multiple quality levels and decay rates. The model is formulated using optimal control theory, and shows that the optimal acquisition strategy depends on the manufacturing-remanufacturing cost difference and price sensitivity of the return response function for high and low quality used products. The sensitivity analysis indicates that in general it is beneficial to obtain a higher rate of high quality returns in the beginning of the planning horizon, and a higher rate of low quality returns towards the end. The fluctuation in demand is mainly absorbed by manufacturing new products and much less by remanufacturing returns. Within the optimal buy-back policy, the result has indicated that it is the acquisition of high quality of returns that mirror the fluctuation in the demand, while the acquisition of low quality of returns show a relatively stable trend.